A review: Effects of estrogen and estrogen receptor modulators on leptin resistance: Mechanisms and pathway. (September 2022) - Farhadi, Zeinab; Azizian, Hossein; Haji-Seyed-Javadi, Ramona; Khaksari, Mohammad
Abstract: Obesity is characterized by an increase in food intake and a decrease in energy expenditure, which causes the accumulation of fat in the body, resulting in various disorders such as type 2 diabetes and cancer. Adipocytes secrete the hormone leptin, and leptin signaling plays an essential role in regulating energy balance. Leptin reduces food intake and increases energy expenditure by binding to its receptors in the hypothalamus and regulating appetite-regulating neurons. Accumulation of excess fat along with increased blood levels of leptin impairs the passage of leptin across the blood-brain barrier and induces leptin resistance. Estrogen also plays an important role in regulating energy balance due to the expression of its receptors in the hypothalamus, and its deficiency is associated with increased food intake and body weight, and estrogen therapy is able to partially mimic the effects of leptin. In this review, we get familiar with the concept of leptin resistance and its mechanisms, and finally, we examine the role of estrogen by emphasizing the mechanisms of energy balance regulation. Highlights: Increased inflammation and high levels of leptin in obesity lead to leptin resistance. Estrogen via ERα increases p-STAT3 signaling in the ARC of hypothalamus and reduces leptin resistance. Estrogen via ERα reduces inflammation, NPY, and AgRP levels and increases α-MSH. Tamoxifen as a SERM, reduces leptin resistance by reducing inflammation and modulating brain neuropeptides. Aging is an influential factor contributing to leptin responsiveness in presence of estrogen, which reduces the effects of estrogen.